ĐIỀU CHẾ VÀ TÍNH CHẤT CỦA 5-(4-AXETAMIDO-2-CLOARYL)-1,3,4-OXADIAZOL-2-THIOL - Sơn, Nguyễn Thị; Tú, Hà Minh; Bôi, Lưu Văn (Vietnam Journal of Chemistry, 2012)
Thiocarbamoylation 4-acetamido-2-chlorobenzoyl hydrazide by tetramethylthiuram disulphide (TMTD) afforded 5-(4-acetamido-2-chlorophenyl)-1,3,4-oxadiazole. Reaction of the later with N-a-cloacetanilide derivatives run into two alternative ways. In the alkaline solution 2-arylamino-5-(acetamido-2-chlorophenyl)-1,3,4-oxadiazole has been isolated, but in the neutral medium 2-(N-carboxamidoarylmethylthio)-5-(4-acetamido-2-chlorophenyl)-1,3,4-oxadiazole have been obtained as the main product. The structures of the products have been confirmed by the spectroscopic data and the biological activities have been tested.